The Readiness of the Level 3 Nursing Students of University of Luzon in Their Operating Room Experience - Flores, Joelle Shaine; Fernandez, Bernadeth; Canta, Heart Nicole; Peleglorio, Charllote; Cave, Liam Joshua; De Jesus, Christian; Beltran-Villar, Johanna (MALATA SAINS INDONESIA, 2025)
Introduction: Operating rooms, often referred to as the